Boron nitride materials as emerging catalysts for oxidative dehydrogenation of light alkanes. (22nd October 2022) - Xu, Chenyang; Ge, Cong; Sun, Dandan; Fan, Yining; Wang, Xue-Bin
Abstract: Light olefins (C2 –C4 ) play a crucial role as basic ingredients in chemical industry, and oxidative dehydrogenation (ODH) of light alkanes to olefins has been one of the popular routes since the shale gas revolution. ODH of light alkanes has advantages on energy-and-cost saving as compared with traditional direct dehydrogenation, but it is restricted by its overoxidation which results in the relatively low olefin selectivity. Boron nitride (BN), an interesting nanomaterial with an analogous structure to graphene, springs out and manifests the superior performance as advanced catalysts in ODH, greatly improving the olefin selectivity under high alkane conversion. In this review, we introduce BN nanomaterials in four dimensions together with typical methods of syntheses. Traditional catalysts for ODH are also referred as comparison on several indicators—olefin yields and preparation techniques, including the metal-based catalysts and the non-metal-based catalysts. We also surveyed the BN catalysts for ODH reaction in recent five years, focusing on the different dimensions of BN together with the synthetic routes accounting for the active sites and the catalytic ability. Finally, an outlook of the potential promotion on the design of BN-based catalysts and the possible routes for the exploration of BN-related catalytic mechanisms are proposed.